Jual Beli Online Dengan Menggunakan Sistem Cash On Delivery Di Kelurahan Kalangan di Tinjuan Kompilasi Hukum Ekonomi Syariah - Afifah Nusrhoh; Agustina Damanik (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The problem in this study is how the practice of buying and selling online with the cash on delivery system is seen from the compilation of sharia economic law. This research is field research with a qualitative approach, the primary data source is from couriers and buyers while secondary data comes from documents related to this research, then data collection techniques through observation, interviews and documentation and data analysis techniques use descriptive qualitative. The results of this study explain that in buying and selling online, khiyar must be formed which has been implemented or carried out by sellers and buyers, namely Khiyar Disgrace and Khiyar Terms. It's the same as buyers who suffer losses because the goods they ordered are damaged, so they may return, and Khiyar. This condition applies if the conditions put forward by the seller have conditions to be allowed to return if they are not in accordance. Review of Compilation of Sharia Economic Laws regarding khiyar rights in buying and selling online in the COD system, the law is permissible, where it has been categorized as a type of buying and selling Bai'i As Salam. And the payment can also be made later when the goods ordered arrive at the destination address. Based on this, the explanation in the Compilation of Sharia Economic Law. Furthermore, it is not included in buying and selling transactions which are prohibited in Islam as explained in the previous chapter.